The Relationship Between Cognitive Resource Consumption During Gameplay and Postgame Aggressive Behaviors: Between-Subjects Experiment - Huina Teng; Lixin Zhu; Xuanyu Zhang; Boyu Qiu (JMIR Publications, 2023)
Abstract BackgroundThe question of how video games can shape aggressive behaviors has been a focus for many researchers. Previous research has focused on how violent video game content leads to postgame aggressive behaviors. However, video games not only convey violence or prosocial content to players but also require cognitive effort from individuals. Since human cognitive resources are limited, consuming more cognitive resources in a game leads to less cognitive resources to suppress aggressive impulses. Therefore, the depletion of cognitive resources from playing video games may also lead to changes in postgame aggressive behaviors. ObjectiveThis study aimed to examine the relationship between cognitive resources consumed in video games and postgame aggressive behaviors. MethodsA total of 60 participants (age: mean 20.22; range 18-24 y) were randomly assigned to either the high-load group or the low-load group. Participants from both groups played a video game centered around college life. In the low-load group, participants followed the gameplay instructions to complete it. In the high-load group, participants were given an extra digital memory task to complete while playing the game. Participants in both groups played the video game for about 25 minutes. A maze selection task was then conducted to measure the participants' helping and hurting behaviors. ResultsThe independent samples 2-tailed tt58Pdt58Pd ConclusionsAs more cognitive resources are consumed in a video game, more hurting behaviors are exhibited after the game. This finding proposes an alternative route by which video games impact aggressive behaviors, adding to previous theories and raising concerns about the popularity of cognitive training games.